Potensi Agrowisata Kebun Stroberi Melky di Nagari Balingka Kecamatan IV Koto Kabupaten Agam - Nurfitri, Widia; Mariya, Sri (Lembaga Yasin AlSys, 2025)
This study originates from the need to develop agrotourism destinations based on local potential, particularly in the context of Melky Strawberry Farm in Agam Regency. The objectives of the research are to: (1) analyze the potential of Melky Strawberry Farm as an agrotourism destination; (2) evaluate the level of accessibility to the location; and (3) assess the condition of available facilities and infrastructure. A descriptive qualitative method was employed, with data collected through observation, in-depth interviews, and documentation. Informants included the farm owner, visitors, local community members, and village government officials. Data were analyzed using the interactive model of Miles and Huberman, comprising data reduction, data display, and conclusion drawing, with data validity ensured through source and method triangulation. The findings indicate that Melky Strawberry Farm holds significant potential for development as a nature-based and educational agrotourism destination, offering key attractions such as scenic natural views, a cool climate, and strawberry-picking activities. Its strategic location along the Bukittinggi–Sicincin route via Malalak offers strong accessibility advantages. However, the development of the destination faces challenges, including limited supporting facilities, the absence of formal institutional structures, and an unstructured promotional strategy. The study recommends strengthening institutional governance, improving tourism infrastructure, and optimizing digital promotion to establish Melky Strawberry Farm as a leading agrotourism destination in Agam Regency.